Play for Early Childhood Character Development: A Systematic Review and Meta-analysis - R Rezki; G Gusril; A Asril (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to provide a review of developing child character through playing activities. Providing a playing space for children might help them instill their characters properly. Playing while learning and learning while playing are the principles of child learning. Playing is an important aspect to stimulate all child development, including the development of religious and moral values, cognitive, language, social-emotional, physical-motor, and artistic aspects. This study used library research methods to describe the trend of research in physical education in the last five years (2018–2022). Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were adopted for the research review. Scopus was used as the database in the article search. The article search obtained 385 articles retrieved from the database. After following the exclusion criteria, only 12 articles remained. The study succeeded in analyzing: 1) playing, and exercise for a child’s character development, 2) character for early childhood, and 3) character development through education and parents.